Comparison between effectivity of povidone Iodin 1% application with swab technique and rinse to the number of bacteria colonization as an aseptic action in the Department of Oral and Maxillofacial Surgery, Faculty of Dentistry, Universitas Sumatera Utara - Hendry Rusdy; Indra B. Siregar; Nur Syamimi; Isnandar (Journal of Dentomaxillofacial Science, 2020)
Objective: To compare between Effectivity of Povidone Iodin 1% Application With Swab Technique and Rinse To the Number of Bacteria Colonization As An Aseptic Action at the department of oral surgery, Faculty of Dentistry, Universitas Sumatera Utara.Material andÂ  Methods: This was an experimental study with post-test only control group design approach. Purposive technique is applied to collect samples which are clinical students. In this study, sample were divided into 4 groups and each consisting of 10 people. The sample was divided into negative control group with 0.9% normal saline and 1% povidone iodine treatment group with two techniques which is swab and gargle.Results: Based on Mann-Whitney test result on 1% Povidone Iodin group which was rinse andÂ  swab technique obtained p-value = 0.382 where p-value > 0,05 so it can be concluded that there is no significant difference between 1 % Povidone Iodine in rinsing technique and 1% Povidone Iodine in swabbing.Conclusion: Rinsing was more effective than swab as an aseptic action with 1% Povidone Iodine.